If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -212 = -2 + -6(5v + -2) Reorder the terms: -212 = -2 + -6(-2 + 5v) -212 = -2 + (-2 * -6 + 5v * -6) -212 = -2 + (12 + -30v) Combine like terms: -2 + 12 = 10 -212 = 10 + -30v Solving -212 = 10 + -30v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '30v' to each side of the equation. -212 + 30v = 10 + -30v + 30v Combine like terms: -30v + 30v = 0 -212 + 30v = 10 + 0 -212 + 30v = 10 Add '212' to each side of the equation. -212 + 212 + 30v = 10 + 212 Combine like terms: -212 + 212 = 0 0 + 30v = 10 + 212 30v = 10 + 212 Combine like terms: 10 + 212 = 222 30v = 222 Divide each side by '30'. v = 7.4 Simplifying v = 7.4
| 3(4-7)=-21+12z | | 5-[(-4)-1]=10-x | | x^3+2x^3=72 | | v^2-16-6v=0 | | -4y-1(5y+6)=-7y+3 | | -2(8n+1)-4(n+5)=-2 | | 2/3(3x-9)=1/4(4x-12) | | 13r-8-12= | | 10x+5+8=12x-3x+8 | | 9=4x-x | | 6(1-2m)-4(m+1)=50 | | v=x(19-2x)(8.5-2x) | | 600=4x+8x | | 600=4x*8x | | -143=-11*x | | -6(5-7r)+4(-4r-5)=28 | | 15x-3-4x=21x-8-25 | | 4(x)-4(2x)=600 | | 3x+5x-5=2(4x+1) | | -9+4r=4t-3-6 | | 3x^3-4x^2+9x-12=0 | | 1+4x+8x=-11 | | -17*x=-204 | | (x+3)/5=(3x+1)/4 | | 12x+1=12x-6 | | 8(x-2)+4x=9(x+5)-22 | | 3(x-1)=2x-3+x | | 2x-3/2x+x+3/3x | | 2y=60k | | X/2-1/3=8 | | 2v+18=16-4-(v+7) | | 3x+2=18-x |